A New Method for Inextensible Flows of Timelike Curves in Minkowski Space-Time E14. (16th December 2014) - Körpinar, Talat
Abstract : We construct a new method for inextensible flows of timelike curves in Minkowski space-time E 1 4 . Using the Frenet frame of the given curve, we present partial differential equations. We give some characterizations for curvatures of a timelike curve in Minkowski space-time E 1 4 .